Penentuan Umur Simpan Ikan Kembung (Rastrelliger kanagurta) Asin dengan Metode Accelerated Shelf Life Testing (ASLT) - Puspasari, Erna; Nurlaela, Raden Siti; Hapsari, Distya Rizki; Rohmah, Salma Amiatri; Aprialdi, Muhammad Agung (Universitas Djuanda, 2025)
ABSTRACT Mackerel is a highly nutritious fish with significant economic value and is widely consumed in large quantities. Compared to other animal-based meats, fish is particularly perishable due to its high water content, ranging from 60% to 70%. This study aims to determine the shelf life of salted mackerel, estimate its shelf life, and asses changes in quality parameters. Salted mackerel was stored in polypropylene plastic packaging for four weeks at three different temperatures, namely room temperature (20-22°C), 30°C, and 40°C. Weekly tests were conducted to analyze moisture content, total plate count, sensory properties (color, the characteristic salted fish aroma, rancid aroma, and texture), and hedonic attributes (color, aroma, and texture). During storage, the quality of salted mackerel exhibited variation, with sensory and hedonic characteristics declining over time. In contrast, moisture content and the total plate count showed an increasing trend. Among the sensory quality parameters, the characteristic aroma of salted mackerel emerged as a critical parameter. The shelf life of salted mackerel under varying storage temperatures was determined based on the lowest activation energy value, with a shelf life of 105 days at room temperature (20–22°C), 91 days at 30°C, and 84 days at 40°C. Keywords: ASLT, mackerel, salted fish, shelf life ABSTRAK Ikan kembung merupakan ikan yang sangat bergizi yang memiliki nilai ekonomi yang signifikan dan dikonsumsi dalam jumlah banyak. Dibandingkan dengan daging hewan lainnya, bahan baku yang sangat mudah rusak adalah ikan karena mengandung persentase air yang tinggi antara 60-70%. Tujuan penelitian ini adalah untuk mengetahui umur simpan ikan kembung asin, memperkirakan umur simpannya, dan memeriksa perubahan kriteria mutu. Menggunakan kemasan plastik polypropylene, ikan kembung asin disimpan selama empat minggu pada tiga suhu berbeda, yaitu suhu kamar (20-22°C), 30°C, dan 40°C. Setiap minggu tes dilakukan pada kadar air, jumlah piring total, sensorik (warna, aroma khas ikan asin, aroma, dan tekstur), dan hedonik (warna, aroma, dan tekstur). Selama penyimpanan, kualitas ikan kembung asin bervariasi sementara karakteristik sensori dan hedonik menurun dengan penyimpanan, ukuran kualitas kadar air meningkat dan Total Plate Count meningkat. Parameter kualitas sensori dari aroma ikan kembung asin yang khas menjadikannya parameter penting dalam ikan kembung asin. Umur simpan ikan kembung asin pada suhu penyimpanan yang berbeda dapat dipastikan dari nilai energi aktivasi terendah, yaitu 105 hari pada suhu kamar (20–22°C), 91 hari pada suhu 30°C, dan 84 hari pada 40°C.